Penerapan Model Hands On Activity untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik pada Pembelajaran Fisika MTSN IV Koto Aur Malintang - Erti, Murni Puji (Universitas Islam Negeri Imam Bonjol Padang, 2017)
This research is motivated by the lack of critical thinking skills of learners in the learning process of physics in MTsN IV Koto Aur Malintang. This leads to physics learning outcomes learners are still under KKM set is 75. Among the causes is the lack of an opportunity for learners to develop thinking skills, especially critical thinking skills, students are less active in developing her potential, as well as the learning process used is more teacher-centered. Businesses that can be done to improve the critical thinking skills of learners is to implement a model of hands on activity. This study aims to determine the increase in critical thinking skills of learners by applying the model of hands on activity on learning physics MTsN IV Koto Aur Malintang.This study is a quasi-experimental research (quasy-exsperimental research) research design is randomized control group only design. The population in this study were all students of class VII MTsN IV Koto Aur Malintang Academic Year 2016/2017. The sampling in this class using cluster random sampling technique. Retrieved class as a class experiment VII.1 and VII.2 class as the control class. The instrument used in this study is a test of learning outcomes in the form of an objective test to use traditional indicators of critical thinking. The technique used to test the hypothesis is by using t-test. T tests were performed for normal distribution of data and data group has a homogeneous variance.Based on data analysis averages the critical thinking skills of students in the experimental class was 69.15 and in control group was 62.89. The results of the analysis of data obtained through t test t = 2.63 and 1.66 t table, where t count> t table (2.63> 1.66). His decision is H0 and H1 accepted. This means learning model application hands on activity in the learning of physics can improve critical thinking skills of students in learning physics MTsN IV Koto Aur Malintang. So it can be concluded that the application of the model hands-on activity can improve critical thinking skills of students in learning physics MTsN IV Koto Aur Malintang at level of 95%.